2019
DOI: 10.1001/jamapediatrics.2018.2302
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Reinterpreting Previously Reported Genomic Epilepsy Test Results for Pediatric Patients

Abstract: IMPORTANCE Clinical genomic tests that examine the DNA sequence of large numbers of genes are commonly used in the diagnosis and management of epilepsy in pediatric patients. The permanence of genomic test result interpretations is not known. OBJECTIVE To investigate the value of reinterpreting previously reported genomic test results. DESIGN, SETTING, AND PARTICIPANTS This study retrospectively reviewed and reinterpreted genomic test results from July 1, 2012, to August 31, 2015, for pediatric patients who pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 15 publications
4
32
4
Order By: Relevance
“…Neonatal-onset epilepsies (57%) followed by epileptic encephalopathies (32%) were most frequently diagnostic. Interestingly, in this study only 3% of cases reported had a variant of uncertain significance (VUS), whereas other studies have identified a VUS in >30% of cases (Lindy et al 2018; SoRelle et al 2018). This large difference in VUS detection rate probably can be attributed to differences in variant interpretation criteria; the use of recently published standardized interpretation guidelines (Richards et al 2015) shows a high rate of VUS detection in epilepsy panel studies (SoRelle et al 2018).…”
Section: Types Of Genomic Testingcontrasting
confidence: 73%
See 1 more Smart Citation
“…Neonatal-onset epilepsies (57%) followed by epileptic encephalopathies (32%) were most frequently diagnostic. Interestingly, in this study only 3% of cases reported had a variant of uncertain significance (VUS), whereas other studies have identified a VUS in >30% of cases (Lindy et al 2018; SoRelle et al 2018). This large difference in VUS detection rate probably can be attributed to differences in variant interpretation criteria; the use of recently published standardized interpretation guidelines (Richards et al 2015) shows a high rate of VUS detection in epilepsy panel studies (SoRelle et al 2018).…”
Section: Types Of Genomic Testingcontrasting
confidence: 73%
“…Periodic reanalysis of existing genetic data is not performed by all clinical laboratories. However, studies have shown that genetic diagnoses may significantly change over time (Costain et al 2018; Hiatt et al 2018; Mersch et al 2018; SoRelle et al 2018). The types of diagnostic changes include not only upgrades from uncertain diagnosis to disease-causative diagnosis, but also can include downgrades from pathogenic diagnoses to benign findings.…”
Section: Technical Limitations and Pitfallsmentioning
confidence: 99%
“…Any discrepancy should be reviewed by both the molecular pathologist and clinician, and prior reports should be reviewed. Importantly, recent data suggest that many VUS will eventually be classified as benign (82)(83)(84)(85)(86) and can usually be resolved with subsequent clinical correlations, in discussions between the molecular diagnostician, clinician, and the patient.…”
Section: Genetic Data Analysismentioning
confidence: 99%
“…Yet interventions making use of this new information have been limited, and a problematic side effect, especially for family members, is that estimates of the penetrance of pathogenic DNA variants decline as more unaffected individuals are screened. Reclassification of variants initially thought to be pathogenic has proven to be a common problem (5).…”
Section: A Genetic Revolution In Medicine?mentioning
confidence: 99%